Antimicrobial Efficacy of Different Herbal Extracts against Root Canal Pathogens - An in Vitro Study - Maryam Raoof; Mohammad H. Zadeh; Zahra E. Nejad; Fariba Sharififar; Mansooreh Khodashenas; Rahim Fereidooni (Indian Journal of Dental Research)
Background: The antimicrobial activity exhibited by the plant extracts against various pathogens has previously been demonstrated to a limited extent. However, the antibacterial effects of most of them have not yet been clarified in endodontics. Aim: This study aimed to determine the antimicrobial activity of some medicinal plants' methanolic extracts against some root canal microorganisms. Methods and Materials: In this in vitro study, after gathering the five plants (pomegranate peel, clove, Zhumeria majdae, Eucalyptus galbie and green tea), their methanolic extracts were obtained by the maceration method, and the antimicrobial activity was determined using micro- and macro-dilution methods. The microorganisms tested in this study were Enterococcus (E.) faecalis, Porphyromonas (P.) gingivalis and Fusobacterium (F.) nucleatum. Non-ready-to-use calcium hydroxide (CH), ready-to-use Calcipex II CH and methanol were used as control materials. Statistical Analysis: The nonparametric Kruskal–Wallis and Friedman tests were used to analyse and evaluate the data and variables. Results: In all concentrations and time intervals studied, eucalyptus extract showed the highest antimicrobial activity against E. faecalis. All the extracts showed growth-inhibitory effects against P. gingivalis and F. nucleatum. There were no significant differences between the anti-enterococcus effects of eucalyptus extracts and non-ready-to-use CH (P > 0.05). Conclusion: There was a greater efficacy of Eucalyptus galbie extract than other extracts.